Ludwig Senfl: Motets For Five Voices. (Hollitzer Verlag, 2022)
In this volume of the NSE, all five-part motets by Ludwig Senfl are published for the first time. It contains Marian motets such as Mater digna Dei / Ave, sanctissima Maria, which reflect the deep Marian devotion at the court of Duke Wilhelm IV, psalm motets in which Senfl sometimes refers to Josquin Desprez in different ways (e.g. Miserere mei, Deus), or works like Qui prophetice prompsisti, whose Tertia pars Vita in ligno moritur was extraordinarily widespread in the 16th century. In addition, the volume offers for the first time an edition of Senfl's large-scale Te Deum laudamus as well as various multi-text motets. Compositions such as Christ resurgens ex mortuis / Christ has risen show the points of contact between the spiritual Latin and vernacular spheres, other works - for example the Tanto tempore vobiscum / Philippe qui videt me - follow the tradition of the cantus firmus motet, in which Senfl enrolls sustainably. In the present volume of the NSE, all of Ludwig Senfl's five-part motets are published for the first time. It includes Marian motets such as Mater digna Dei / Ave, sanctissima Maria reflecting the Marian devotion at the court of Duke Wilhelm IV, psalm motets that refer to Josquin Desprez in various ways (e. g. Miserere mei, Deus), or works such as Qui prophetice prompsisti, whose tertia pars Vita in ligno moritur was widespread during the sixteenth century.In addition, the volume offers the first edition of Senfl's large-scale Te Deum laudamus as well as several polytextual motets. Compositions such as Christus resurgens ex mortuis / Christ ist erstanden show the points of contact between the sacred Latin and the vernacular spheres, while other works — for example Tanto tempore vobiscum / Philippe qui videt me — take up the long tradition of the cantus firmus motet , into which Senfl inscribes himself with lasting effect.